Protonation-State-Dependent Communication in Cytochrome c Oxidase - Helabad, Mandi Bagherpoor; Ghane, Tahereh; Reidelbach, Marco; Woelke, Anna Lena; Knapp, Ernst Walter; Imhof, Petra (Biophysical Journal, 2017)
Proton transfer in cytochrome c oxidase from the cellular inside to the binuclear redox center (BNC) can occur through two distinct pathways, the D- and K-channels. For the protein to function as both a redox enzyme and a proton pump, proton transfer into the protein toward the BNC or toward a proton loading site (and ultimately through the membrane) must be highly regulated. The PR → F transition is the first step in a catalytic cycle that requires proton transfer from the bulk at the N-side to the BNC. Molecular dynamics simulations of the PR → F intermediate of this transition, with 16 different combinations of protonation states of key residues in the D- and K-channel, show the impact of the K-channel on the D-channel to be protonation-state dependent. Strength as well as means of communication, correlations in positions, or communication along the hydrogen-bonded network depends on the protonation state of the K-channel residue K362. The conformational and hydrogen-bond dynamics of the D-channel residue N139 is regulated by an interplay of protonation in the D-channel and K362. N139 thus assumes a gating function by which proton passage through the D-channel toward E286 is likely facilitated for states with protonated K362 and unprotonated E286. In contrast, proton passage through the D-channel is hindered by N139's preference for a closed conformation in situations with protonated E286.
CRIS-Team Scopus Importer:2020-02-18